Optimalisasi Peran Mahasiswa KKNT Sebagai Tenaga Pengajar dalam Meningkatkan Pendidikan di Desa Grujugan - Taufiq, Azzahra’ Rahita; Setyawan, Agung; Citrawati, Tyasmiarni; Hardiansyah, Rila (Lembaga Citra Pustaka, 2024)
Education is one of the most important things in life, sometimes education is a measure of caste in society. In the educational process there is such a thing as teaching and being taught. Our Thematic Real Work Lecture (KKN-T) was held in Grujugan village, Pamekasan Regency. Our aim in carrying out KKNT in the village is to help improve the quality of education for children in the village. Many of the teaching staff there are already old so it is very difficult to follow the development of children who are very active in learning, as a result the learning process is less than optimal. Thus, this article has the title Optimizing the Role of KKNT Students as Teaching Personnel in Improving Education in Grujugan Village. The results of our KKNT activities provide an illustration of the enthusiasm and enthusiasm of the children regarding the role of students as teaching staff in helping education in Grujugan village through educational activities.